A Comparative Study of Physiological and Physical Parameters Between Married Females Residing at The Qushtapa Refugee Camp and in The City of Erbil in Kurdistan-Iraq - Qarani, Sozan M.; Qasim, Firas Kh.; Abdulrahman, Mahde S. (Science Journal of University of Zakho, 2021)
Refugees are under a high-risk factor of being suffering from many different diseases due to the uncontrolled accommodations environment of the camps. This study aimed to test whether the camp’s habitat affecting the physical activities of the married females as a biomarker of the adverse effects on the health management issues. 60 married females (30 refugees and 30 city residents) were recruited. Blood samples of all participants were analyzed for blood glucose, blood triglycerides, blood cholesterol, blood hemoglobin (HGb), blood heamatocrite percentage (HCT %) and other physical parameters estimated like body mass index (BMI), mean arterial pressure (MAP). Additionally, participants were screened for bacterial UTIs. Refugees married females showed a significant decrease in the blood hemoglobin concentration (gm/dl) compared with the city females (P= 0.014) and blood heamatocrite percentage (HCT %) (P= 0.0074). Also, no significant differences were observed for the other parameters between refugees married females and city married females. The UTI bacterial infection in refugees married females (21, 65.6%) was significantly higher than the infection among city resident married females (11, 34.4%) (P=0.0096). The higher incidence percentage of UTIs were caused by Gram-negative bacteria (87.5%). The most dominant pathogen which established UTIs was Escherichia coli (57%). A high-stress level of camp environment and nutritional malformation may affect the refugees married females more than the city females. Therefore, it is the international community responsibility to protect and provide life-saving assistance to all refugee women and to those that have been subjected to such situations.